Synthesis, Characterization and Applications of Sustainable Advanced Nanomaterials (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue highlights the last decade’s progress regarding new nanostructured materials. In this regard, the development of nanoscale syntheses and innovative characterization tools resulted in the tailored design of nanostructured materials with versatile abilities in many applications were investigated. Various types of engineered nanostructures, usually metal nanoparticles or nanoporous metal oxides, have been synthesized for various applications. This Special Issue covers the state-of-the-art of advanced nanoparticles in many disciplines (chemistry, pharmacy, nano-medicine, agriculture, catalysis, and environmental science). The Special Issue entitled, Synthesis, Characterization and Application of Sustainable Advanced Nanomaterials, including 18 original research works, focuses on highlighting the progress, challenges, and future directions in the area of the synthesis and characterization of nanomaterials and nanostructures with multiple applications in chemistry, physics, biology, and medicine [1-3].